Effect of moisture on in situ transesterification of microalgae for biodiesel production. Issue 1 (20th June 2013) - Sathish, Ashik; Smith, Brian R.; Sims, Ronald C.
Abstract Background A major hurdle with algal biodiesel production has been the energy required to dry algal biomass prior to lipid extraction and/or conversion. Water interferes with the extraction and/or conversion of algal lipids to biodiesel. The focus of this study was to evaluate the efficiency of the in situ transesterification method for biodiesel recovery when processing algal biomass with varying amounts of moisture and to evaluate changes in efficiency as in situ transesterification reaction parameters were varied. Results Results indicated that moisture content affected biodiesel recovery. Specifically, algal biomass moisture contents above 20% by mass led to statistically significant reductions in biodiesel recovery. However, increasing the amount of catalyst and/or methanol in the reaction resulted in higher recoveries when using wet algal biomass containing 84% moisture. Using 10% (v/v) sulfuric acid in methanol with the wet biomass to solution ratio of 25 mg (dry mass equivalent) mL‐1 resulted in the recovery of approximately 81% of the maximum biodiesel yield. Conclusion This study showed that the presence of moisture at greater than 20% by mass in algal biomass significantly decreased biodiesel recovery when using in situ transesterification. Increasing the amount of methanol and/or catalyst in the reaction improved biodiesel recovery from wet algal biomass. © 2013 Society of Chemical Industry